2015
DOI: 10.1152/ajpheart.00155.2015
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in arterial stiffening and dysfunction in Western diet-induced obesity

Abstract: , is an independent predictor of cardiovascular event risk. Recent evidence demonstrates that accelerated aortic stiffening occurs in obesity; however, little is known regarding stiffening of other disease-relevant arteries or whether regional variation in arterial stiffening occurs in this setting. We addressed this gap in knowledge by assessing femoral PWV in vivo in conjunction with ex vivo analyses of femoral and coronary structure and function in a mouse model of Western diet (WD; high-fat/high-sugar)-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 51 publications
9
54
0
Order By: Relevance
“…These findings are of considerable translational importance given that obesity and insulin resistance are strongly associated with cardiovascular stiffness, especially in females. 16,2527 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are of considerable translational importance given that obesity and insulin resistance are strongly associated with cardiovascular stiffness, especially in females. 16,2527 …”
Section: Discussionmentioning
confidence: 99%
“…24 However, to date, the effect of exercise on endothelial stiffness associated with diet-induced obesity has not been examined. Herein, using a female mouse model of WD-induced obesity, insulin resistance and cardiovascular stiffness, 16,17,2527 we tested the hypothesis that regular volitional exercise would reduce stiffness in the aortic endothelium, as assessed by AFM in aortic explants, as well as reduce in vivo aortic stiffness, as assessed by pulse wave velocity (PWV). Furthermore, we hypothesized that changes in aortic stiffness produced by exercise would be accompanied by a reduction in oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern of microvascular remodeling is also in contrast to that observed in larger conduit vessels. Here, obesity has been associated with increased vessel stiffness (6,52) and linked to the development of hypertension (62). While microvascular remodeling is not a prerequisite for hypertension (22), it does shape the nature of remodeling, as evidenced by the finding that microvascular stiffness was decreased in hypertensive, but not normotensive, obese humans (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…While clinical studies have shown that the stiffness of one vascular bed (e.g., human aorta) correlates with the stiffness of another (e.g., human carotid artery) (5), the work of Bender et al (3) suggests that this is not universally applicable. Perhaps the discrepancy lies in data generated in humans versus mouse, or perhaps it lies in the temporal or cumulative effect of exposure to a Western high-fat diet.…”
mentioning
confidence: 99%